Homocysteine sensitizes the mouse neuromuscular junction to oxidative stress by nitric oxide. Issue 12 (15th August 2018) - Wang, John S.; Bojovic, Danica; Chen, Yang; Lindgren, Clark A.
Abstract : Homocysteine (HCY), a redox-active metabolite of the methionine cycle, is of particular clinical interest because of its association with various neurodegenerative diseases including amyotrophic lateral sclerosis. It has been previously established that HCY exacerbates damage to motor neurons from reactive oxygen species (ROS) such as hydrogen peroxide. To assess the role of HCY at the mammalian neuromuscular junction, neurotransmission was monitored by electrophysiology at the mouse epitrochleoanconeus muscle. Preparations were preincubated in HCY before inducing ROS and recordings were taken before and after ROS treatment. In this study, HCY was observed to sensitize the neuromuscular junction to ROS-induced depression of spontaneous transmission frequency, an effect we found to be mediated by a N -methyl-D-aspartate receptor (NMDAR) and nitric oxide (NO). The NMDAR antagonist D, L-2-amino-5-phosphonopentanoic acid prevented the HCY-induced sensitization to oxidative stress. Disrupting NO activity with either the nitric oxide synthase I antagonist Nω-nitro-L-arginine methyl ester hydrochloride or the NO scavenger 2-(4-carboxyphenyl)-4, 4, 5, 5-tetramethyl-imidazoline-1-oxyl-3-oxide potassium salt also prevented sensitization. Moreover, replacing HCY with the exogenous NO donor Diethylamine NONOate diethylammonium was sufficient to reconstitute the effects of HCY-induced sensitization to ROS. Interestingly, a novel secondary effect was observed where HCY itself depresses quantal content, an effect found to be mediated by NMDARs independently of nitric oxide and ROS. Collectively, these data present a novel model of two distinct pathways through which HCY alters neurotransmission at the neuromuscular junction. Characterizing HCY's mechanism of action is of particular clinical relevance as many treatments for amyotrophic lateral sclerosis are centered on mitigating HCY-induced pathologies.